2016
DOI: 10.1108/jpmh-12-2015-0052
|View full text |Cite
|
Sign up to set email alerts
|

A survey of community pharmacists’ attitudes towards mental illness

Abstract: Purpose – The purpose of this paper is to compare the pharmacy services provided to people taking psychotropic and cardiovascular medications and examine the association between pharmacists’ attitudes towards mental illness and provision of pharmacy services. The paper also considers pharmacists’ opinions of the pharmaceutical care needs of people with mental illness including their physical health. Design/methodology/approach – A survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…Meanwhile, significantly lower pharmaceutical services was provided to mentally ill patients in a previous study. 37 Several previously observed barriers may have created the gap. [11][12][13] Findings from the study also showed positive perception of respondents' therapeutic relationship with the patients, which corroborates findings from a previous study in Jordan.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Meanwhile, significantly lower pharmaceutical services was provided to mentally ill patients in a previous study. 37 Several previously observed barriers may have created the gap. [11][12][13] Findings from the study also showed positive perception of respondents' therapeutic relationship with the patients, which corroborates findings from a previous study in Jordan.…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, significantly lower pharmaceutical services was provided to mentally ill patients in a previous study. 37 Several previously observed barriers may have created the gap. 11-13…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation